2010
DOI: 10.1002/bimj.201000030
|View full text |Cite
|
Sign up to set email alerts
|

A novel definition of the multivariate coefficient of variation

Abstract: The coefficient of variation CV (%) is widely used to measure the relative variation of a random variable to its mean or to assess and compare the performance of analytical techniques/equipments. A review is made of the existing multivariate extensions of the univariate CV where, instead of a random variable, a random vector is considered, and a novel definition is proposed. The multivariate CV obtained only requires the calculation of the mean vector, the covariance matrix and simple quadratic forms. No matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 17 publications
0
59
0
Order By: Relevance
“…Coefficient of variation (CV), the ratio of standard deviation to the mean, was calculated to assess the amount of dispersion and precision by which parameters were measured. 1 All analyses were performed using SAS for Windows (version 9.2, SAS Institute).…”
Section: Discussionmentioning
confidence: 99%
“…Coefficient of variation (CV), the ratio of standard deviation to the mean, was calculated to assess the amount of dispersion and precision by which parameters were measured. 1 All analyses were performed using SAS for Windows (version 9.2, SAS Institute).…”
Section: Discussionmentioning
confidence: 99%
“…For p = 1, Sokal and Brauman [18] already reported that the classical estimator of the CV is negatively 245 biased. In the multivariate context, Zhang [24] also empirically noticed the fact that the classical estimators of the multivariate coefficients of variation that Albert and Zhang [2] considered were all biased under normality.…”
Section: Bias Of the Classical Estimator Of Voinov And Nikulin's MCVmentioning
confidence: 99%
“…For instance, in biology, Van Valen [21] noticed the inadequacy of the univariate CV when dealing with skeletal measurements on mammals. In the context of EQA analyses, Albert and Zhang [2] and Zhang et al [25] also pointed out this particular issue. Another common approach consists in averaging the marginal CV's to obtain an index of global relative dispersion (as in [3]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations